Just War Doctrine: Relevance and Challenges in the 21st Century - Bowyer, D (Department of Defence Management and Security Analysis, 2008)
For nearly two millennia just war doctrine has been central to Western understanding of justified resort to armed force, and on in conduct of war. As the international system developed so the theory was first secularised and then all but rendered obsolete by a legal paradigm that sought first to establish states’ rights and, later, to eliminate armed force as an instrument of international policy all together. In the world order that has emerged after the Cold War, the legal paradigm has been found wanting yet there remains a requirement for resort to force to be justified. Such justification is required at the international level – in order for a state to retain moral standing and be able to exercise ‘soft power’ – at the national level – for the government to retain its legitimacy – and at the individual level – for the moral well-being of those who must fight. Whilst the nature of warfare remains constant – it is about using violence to impose one state’s will upon another, but is an essentially human activity – its chacarter evolves to reflect the age. Contemporary security threats and a changed value-set have made Western governments more interventionist and concern over non-state actors, massdestructive weaponry and the threats emerging from state failure have prompted some to argue a case for preventive war. Western technological dominance and the preference for a different form of asymmetry on the part of the West’s opponents challenge traditional concepts of jus in bello. This is exacerbated by the appearance on the battlefield of a range of new actors and by a tendency – on the part of the West – to attempt to distance soldiers – the ultimate moral agents in conflict – from the battlefield, creating ‘moral distance’ that may undermine our ability to apply proportionality and discrimination.